2014
DOI: 10.4081/ija.2014.581
|View full text |Cite
|
Sign up to set email alerts
|

Perennial grasses as lignocellulosic feedstock for second-generation bioethanol production in Mediterranean environment

Abstract: In this paper the suitability of three perennial, herbaceous, lignocellulosic grasses (Arundo donax, Saccharum spontaneous spp. aegyptiacum and Miscanthus x giganteus) for the production of second-generation bioethanol in semi-arid Mediterranean environment was stud- .9 Mg ha -1 , respectively) and Miscanthus (19.6±2.8 and 17.2±1.6 Mg ha -1 , respectively). Structural polysaccharides of the raw material were higher in Miscanthus (63.4% w/w) followed by Saccharum (61.5% w/w) and Arundo (57.6% w/w). The same tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 43 publications
6
22
0
2
Order By: Relevance
“…In terms of composition for biochemical conversion, fiber content was comparable to that of other monocot species as A. donax, Miscanthus × giganteus, corn stover, wheat straw, rice straw, and switchgrass (Scordia et al, 2014). Our results are similar to the structural polysaccharides composition reported by Scordia et al (2010), who have also shown the potentiality of S. spontaneum spp.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of composition for biochemical conversion, fiber content was comparable to that of other monocot species as A. donax, Miscanthus × giganteus, corn stover, wheat straw, rice straw, and switchgrass (Scordia et al, 2014). Our results are similar to the structural polysaccharides composition reported by Scordia et al (2010), who have also shown the potentiality of S. spontaneum spp.…”
Section: Discussionsupporting
confidence: 91%
“…Hack. ), among others, might help to contain soil erosion in sloping areas, increase carbon storage in the soil, and provide lignocellulosic biomass for energy and advanced biofuels [24,25].…”
mentioning
confidence: 99%
“…In smilo grass, the mean percentage of leaves was 26.5% in 2013 (range 24-29.4) and 15% in 2014 (range 12.3-17.8), 2-3 times higher than the value (8%) reported from miscanthus leaves (Scordia et al, 2014).…”
Section: Populationsmentioning
confidence: 94%
“…The lowest percentage of tillers weight was 48.1% (PM08) in 2013 and 59% in 2014 (PM05). For miscanthus grown in Mediterranean environments, it has been reported that stems constitute about 75% of the standing crop biomass in autumn (Ercoli et al, 1999) and up to 92% in winter (Scordia et al, 2014).…”
Section: Populationsmentioning
confidence: 99%
See 1 more Smart Citation